2001
DOI: 10.1034/j.1600-0609.2001.066005287.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of moxifloxacin in comparison to ciprofloxacin and G‐CSF in a murine model of cyclophosphamide‐induced leukopenia†

Abstract: We analyzed the effect of the two quinolones moxifloxacin and ciprofloxacin on the repopulation of hematopoietic organs and on the production of cytokines by various organs of cyclophosphamide (CP)-induced leukopenic mice. The effect was compared to that of G-CSF. Cyclophosphamide injection induced a severe leukopenia, with nadir at day 4 post-injection. All the quinolone and G-CSF-treated animals showed WBC>500/microL at the nadir, compared to 50% of saline-treated mice. Cyclophosphamide induced a marked decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 23 publications
3
37
0
2
Order By: Relevance
“…On day 4., we observed the reduction of spleen mass, what was in accordance with the discovery by Karp & Szczytkowski [35]. This effect can be related to severe leukopenia, with was deepest on day 4. after injection with CY, as reported by Shalit et al [34]. The increase of the amount of the cells between day 4. and 6. can be explained in two ways: the proliferation of cells in the spleen and the transfer of hematopoietic stem and pro- genitor cells from the bone marrow.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…On day 4., we observed the reduction of spleen mass, what was in accordance with the discovery by Karp & Szczytkowski [35]. This effect can be related to severe leukopenia, with was deepest on day 4. after injection with CY, as reported by Shalit et al [34]. The increase of the amount of the cells between day 4. and 6. can be explained in two ways: the proliferation of cells in the spleen and the transfer of hematopoietic stem and pro- genitor cells from the bone marrow.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, in our observation CY produced temporary fibrosis of spleen deposits of reticulin were seen on the day 2., less visible on day 4. and the normal amounts were observed back on day 6. of the experiment. It was shown, that administration of CY was associated with marked cytopenia in the spleen [33] and directly induced a significant decrease in number of the myeloid progenitors [34]. On day 4., we observed the reduction of spleen mass, what was in accordance with the discovery by Karp & Szczytkowski [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that IL-2, which plays a major role in maturation/development of lymphocytes and monocytes and stimulates natural killer (NK) cell secretion of IFN (Theze et al, 1996) -which in turn stimulates macrophage activation and T-cell differentiation (Borish & Rosenwasser, 1996), is impacted by CTX treatment (Guo et al, 2012). Similarly, GM-CSF, a hematopoietic growth factor pivotal for the regulation of bone marrow progenitor cell proliferation (Gasson, 1991), was also shown to be affected by CTX treatment (Shalit et al, 2001). Expectedly, here, CTX drastically reduced host serum levels of IL-2, IFN, and GM-CSF; these were significantly increased due to co-treatment with the extract.…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory effects of antibiotics include alteration of phagocytosis, chemotaxis, endotoxin release, cytokine production, hematopoietic recovery after immunosuppression, and tumoricidal effects on certain cancer cells. Moreover some antibiotic agents can affect the life spans of cells through the induction or inhibition of apoptosis (6,(8)(9)(10)22).…”
mentioning
confidence: 99%